2000
DOI: 10.1177/0148607100024002113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parenteral Lipid Emulsions With Different Fatty Acid Composition on Immune Cell Functions In Vitro

Abstract: Our results suggest that an olive oil-based lipid emulsion could modulate immune response selectively, maintaining protective immunity and reducing inflammatory response. Olive oil may offer an immunologically neutral alternative to soybean oil for use in parenteral lipid emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(112 citation statements)
references
References 34 publications
3
100
1
8
Order By: Relevance
“…As a natural consequence, this event leads to an imbalanced synthesis of eicosanoids which affects many humoral and cellular immune functions (Goodwin and Ceupens, 1983). Nevertheless, some beneficial effects have shown the application of emulsions containing olive oil as alternative of soybean oil for the use in parenteral nutrition because an olive oil-based lipid emulsion offers protective immunity and reduces inflammatory response (Moussa, 2000;Granato, 2000). In fact, with the purpose of finding a lipid emulsion capable of protecting mononuclear phagocyte system functions, a recent study revealed that the administration of a lipid emulsion enriched with olive oil to animals infected with Escherichia coli is an efficient method for it (Garnacho-Montero, 2002).…”
Section: Clinical Nutrition and Immune Systemmentioning
confidence: 99%
“…As a natural consequence, this event leads to an imbalanced synthesis of eicosanoids which affects many humoral and cellular immune functions (Goodwin and Ceupens, 1983). Nevertheless, some beneficial effects have shown the application of emulsions containing olive oil as alternative of soybean oil for the use in parenteral nutrition because an olive oil-based lipid emulsion offers protective immunity and reduces inflammatory response (Moussa, 2000;Granato, 2000). In fact, with the purpose of finding a lipid emulsion capable of protecting mononuclear phagocyte system functions, a recent study revealed that the administration of a lipid emulsion enriched with olive oil to animals infected with Escherichia coli is an efficient method for it (Garnacho-Montero, 2002).…”
Section: Clinical Nutrition and Immune Systemmentioning
confidence: 99%
“…Proponents of emulsions containing olive oil suggest that it offers an immunologically neutral alternative to soybean oil for use in parenteral nutrition, with the potential benefit of some mild anti-inflammatory effects. While in vitro experiments and animal experiments support this idea (Moussa et al, 2000;Granato et al, 2000) there are, as yet, very few published clinical studies.…”
Section: Mufa In Clinical Nutritionmentioning
confidence: 99%
“…The changes attributed to fatty acid administration include the reduction of lymphocyte proliferation, which is modified by polyunsaturated fatty acids (n-3 or n-6) or monounsaturated fatty acids (n-9). Studies carried out in both humans and animals have revealed that the administration of high levels of dietary n-3 polyunsaturated fatty acids or the inclusion in parenteral regimens of lipid emulsions rich in n-3 or n-9 fatty acids are related to the reduction of lymphocyte proliferation during the supplementation (30,35,53,56,81). Thus, concanavalin-A or lipopolysaccharide-stimulated lymphocytes have reduced the cellular proliferation in assays carried out in vitro or ex vivo in the presence of free fatty acids or in cell cultures from both animals and humans fed dietary lipids, respectively (10,30).…”
Section: Biological Consequences On Immune Functions Attributed To Famentioning
confidence: 99%